Design & Simulation of PV Grid system with Dispatchable Supercapacitor - Bhuvnesh Kumar, Amit Kumar Rohilla, (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper presents a reliable, extended range power storage for grid connected PV systems. The power supply consists of solar PV source, a battery and Super capacitor (SC). Main source of power is battery, and is connected with super capacitor. These are connected at the starting and transient phase like overloading. Photovoltaic cell works for the steady condition. The total effect of such arrangement is to improve travel range, reduced size of battery , enhanced excellent response during overloading condition and  improved battery life .Better performance which gives optimal use of energy, smooth ride and minimum size of sources of energy. Many stand-alone photovoltaic systems need storage device for providing steady state energy to the load when photovoltaicirradiation is not sufficient. Generally, Batteries are used for such application. Thus, providing a large peak current, like starting of motor, degrades plates of battery, results in devastation of battery. An alternate solution of providing heavy current is to connect battery with super capacitors forming an hybrid energy storage system, for which battery could provide steady state energy also the super capacitor can provide the peak power to connected load. A secondary source, solar panel module is available to charge battery and super capacitor.